Development of an Integrated Ontology to Enhance Interoperability for Airports Security Solutions - Aleid, Katia (2020)
The importance of airports’ cybersecurity is being given from the combination of two key components: airports and security. As airports provide transportation among other services to people which are the most valuable cargo, they are also of the biggest investments in any country. Hence, ensuring security of airports is a necessity in any possible aspect. In this context, we aim to overcome the difference in information representation formats used within airports. Thus, facilitating communication and knowledge exchange between different cybersecurity systems and solutions. In this thesis, we are exploring the current state and activities of airports’ cybersecurity as a base for the development process. Also, we discuss the design of an integrated ontology focused on airports’ cybersecurity. After that, the resulting ontology will be checked against the chosen criteria to evaluate its usefulness in achieving the interoperability goal.